Intercultural Language Competence and Business Communication - Golysheva, Valentina (Armenian Folia Anglistika, 2014)
Teaching modern languages for specific purposes requires the investigation of the interaction of language and socio-cultural aspects, the knowledge of which predetermines successful acquisition of intercultural competence by the students. Students studying business language should be recommended to do the research in the theory of language planning namely Political Correctness (PC). Observing politeness strategy, i.e. avoiding direct imposition either in conditional requests or imperatives might be useful for students studying English to be learned as value one. To reduce the level of imposition most English officials prefer to stick to the strategy of disguised imperatives, i.e. rephrase their public messages by employing specific periphrastic expressions in a statement/request/notice/announcement. In the teaching process priorities should be given to introducing the situational language, the speech etiquette in the English and Russian communities; teaching students to assess social responses.
Keywords: intercultural competence; politeness strategy; situational language; speech etiquette; periphrasis; political correctness